Comparative Study of Work Output and Wages of Construction Craftsmen in the Nigerian Public Sector - Lawal, Philip O.; Olayeni, Tunji (Richtmann Publishing, 2011)
Work output of construction craftsmen in the service of the Federal Republic of Nigeria was the focal point of this study,compared on an annual basis to the wages they received. Comparison was also made of the wages in both the private and the publicsectors. The aim of the research was to quantitatively verify the authenticity of the assumption of the general public of Nigeria that theskills of the craftsmen in the public sector were being underutilized. The Federal Government Ministry of Works offices in three of thenorth-central states were used for the survey. Each of the three state field offices had four departments that were having constructioncraftsmen of various trades as the core employees. Each of the twelve heads of departments was interviewed based on preparedquestionnaire, on the volume of direct-labour work the department undertook annually. Records of the wages of the craftsmen wereobtained from the accounts department while some craftsmen filled and returned questionnaire relating to their perception of the work.Percentages were used for data analysis. The results show that the wages of the craftsmen in the public sector were lower than the wagestheir counterparts in the private sector receive until the 1999 when the wages of the former were increased. It was equally found that thevalues of work output of the public sector craftsmen were infinitesimally small when compared to their wages over the period covered by theinvestigation. The employers were actually paying the wages of the craftsmen for work not done.